Process Research and Development for Heterocyclic p38 MAP Kinase Inhibitors - Thiel, Oliver R.; Achmatowicz, Michal; Milburn, Robert M. (Synlett, 2012)
The need to access different heterocyclic cores as part of p38 MAP kinase inhibitors led to the discovery and development of several efficient approaches to three separate classes of heterocycles, namely phthalazines, pyrazolopyridinones, and triazolopyridines. This account summarizes our studies in this field in a comprehensive fashion.1 Introduction2 Synthesis of Phthalazine-Based p38 Inhibitors2.1 Synthesis of Clinical Candidate 22.2 Synthesis of Clinical Candidate 33 Synthesis of Pyrazolopyridinone-Based p38 Inhibitors4 Synthesis of Triazolopyridine-Based p38 Inhibitors4.1 Synthesis through Pd-Catalyzed Benzhydrazide Couplings4.2 Synthesis through Pd-Catalyzed Benzhydrazone Couplings5.0 Conclusions
Keywords: green chemistry; catalysis; heterocycles; Suzuki reaction; process chemistry